2022
DOI: 10.1002/cam4.5329
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of active surveillance for extra‐abdominal desmoid‐type fibromatosis

Abstract: Desmoid-type fibromatosis (DF) is a (myo-) fibroblastic soft tissue tumor that is classified as an intermediate malignancy according to the World Health Organization classification. 1 DF is highly locally invasive and has a high postoperative recurrence rate. It does not cause distant metastasis like soft tissue sarcomas. Additionally, it may spontaneously regress or disappear without any treatment in some patients, thus it has been named an "enigmatic"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A recent prospective study has shown that S45F mutation is associated with tumor progression (HR = 6.24 [95% CI 1.92–20.30]) and suggests the onset of active treatment (AT) during the AS ( 44 ). Compared with tumor diameter, gender, recurrence cases and other clinical factors, S45F mutation is significantly related to 3-year RFS ( 45 ). It has been reported that CTNNB1 mutation types was associated with tumor progression and aggressive treatment with adjuvant radiotherapy was administered accordingly.…”
Section: Biomarkers In Asmentioning
confidence: 99%
“…A recent prospective study has shown that S45F mutation is associated with tumor progression (HR = 6.24 [95% CI 1.92–20.30]) and suggests the onset of active treatment (AT) during the AS ( 44 ). Compared with tumor diameter, gender, recurrence cases and other clinical factors, S45F mutation is significantly related to 3-year RFS ( 45 ). It has been reported that CTNNB1 mutation types was associated with tumor progression and aggressive treatment with adjuvant radiotherapy was administered accordingly.…”
Section: Biomarkers In Asmentioning
confidence: 99%